Strategi Pembelajaran Guru Pendidikan Agama Islam Di SMKN 3 Sukatani Kabupaten Purwakarta - Munawar, Ahmad; Asy'ari, Hasyim (FATAWA: Jurnal Pendidikan Agama Islam, 2023)
This research aims to describe and analyze the learning strategies implemented by PAI teachers at SMKN 3 Sukatani, examine their effectiveness in improving PAI learning outcomes for class XI students, and identify the obstacles faced and the teacher's efforts to overcome them. This research uses a qualitative approach with a case study method. The data collection techniques used were interviews, observation, and documentation. The research results show that PAI teachers at SMKN 3 Sukatani have changed learning strategies from conventional teacher-centered strategies to discovery learning and problem-based learning strategies that are more student-centered. This change positively impacts PAI learning outcomes for class XI students, where students understand the material more easily, can think critically, are active in learning, and can relate the material to real-life contexts. Even though there are still several obstacles in its implementation, PAI teachers continue to try to overcome them with various innovative and adaptive efforts to meet student needs. The results of PAI learning for class This research implies that PAI teachers need to continue to develop their pedagogical competence, especially in selecting and implementing learning strategies that suit student characteristics and the demands of the times, as well as optimizing the use of comprehensive learning and evaluation media to achieve PAI learning goals effectively and efficiently.